Food Hypersensitivity as a Cause of Atopic Dermatitis - Hendra Santoso (Indonesian Pediatric Society, 1994)
Thirty children from infancy to 12 years suffering from atopic dermatitis were evaluated for food hypersensitivity by means of history, skin prick test, total eosinophils count, and elimination of suspected food. Sixteen (53%) patients had history of allergy to suspected food, the other 16 (53%) had ether allergic diseases. Of the 30 patients, 15 (50%) had one of the parents with allergic diseases, and in 3 patients both parents suffered from a1Iergic diseases. Nineteen (6:3-1.) children had atopic dermatitis triggered by food; egg accounted for 400/o, fish for 53-lo and shrimp for 40% for the allergic manifestations. Skin prick test consisted of 20 food allergens was done to all children above 2 years of age, 12 (40%) of the pa1ients showed positive results. This study demonstrated that food hypersensitivity may play a pathogenic role in some children with atopic dermatitis. Appropriate diagnosis and restriction of diet can improve their skin symptoms.